Kematangan Emosi, Percaya Diri Dan Kecemasan Berbicara Di Depan Kelas - Matulessy, Andik (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. The purpose of the research is to know the relationship between the emotional maturity and self confidence related to the students’ nervousness when they speak in front of the class. The subject of this research is 123 of 5th grade students of Petra 5 Christian Elementary School. The result of this research shows that there is a significant correlation between the emotional maturity and self confidence and the students’ nervousness when they speaking front of the class; partially, the result shows that the emotional maturity correlates negatively but it is not significant with the students’ signifycant who speak in front of the class and self confidence, correlates negatively which is significant with the students’ signifycance when they speak in front of the class.Keyword : the nervousness speaking in front of the class, the maturity of the emotional, self confidence